Endgame for Empire : British-Creek Relations in Georgia and Vicinity, 17631776 - Juricek, John T., 1938- (Book collections on Project MUSE., 2015)
John Juricek examines the shifting alliances and growing tensions among Native Americans, estranged colonists, and British officials from 1763 to 1776.